2020
DOI: 10.1111/eip.13006
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of symptom dimensions and duration of untreated psychosis within a staging model of schizophrenia spectrum disorders

Abstract: Aim: Clinical staging of schizophrenia entails a new method that identifies clusters of symptoms and variation in level of remission, with the goal to create a framework for early intervention. Additionally, duration of untreated psychosis (DUP) may influence symptom severity in the first episode of psychosis (FEP) and could necessitate refining of the staging model. However, consistent evidence concerning variation in symptom severity and DUP between stages is missing. Therefore, we evaluated the clinical val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The results showed that, one year later, the majority of the patients were in the same stage and greater improvements occurred in more severe stages (Table 2 ). Recently, Berendsen et al [ 24 ] developed a study whose results support the clinical validation of this staging model. Patients showed significant differences in the severity of negative, positive, and cognitive symptoms between stages.…”
Section: Resultsmentioning
confidence: 85%
“…The results showed that, one year later, the majority of the patients were in the same stage and greater improvements occurred in more severe stages (Table 2 ). Recently, Berendsen et al [ 24 ] developed a study whose results support the clinical validation of this staging model. Patients showed significant differences in the severity of negative, positive, and cognitive symptoms between stages.…”
Section: Resultsmentioning
confidence: 85%
“…So far only few studies investigated the associations between cognitive functioning and stages ( Berendsen et al, 2021 ; Godin et al, 2019 ; Tedja et al, 2017 ). Two studies also showed associations of cognitive deficits with higher stages of illness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors found that baseline cognitive parameters did not predict stage-transition at three-year follow-up( Tedja et al, 2017 ). Lastly, another cross-sectional study found significantly more decline in global cognitive functioning at more advanced disease stages in acutely admitted inpatients with schizophrenia spectrum disorders ( Berendsen et al, 2021 ). The majority of the latter studies were cross-sectional or had a short-term follow-up, which is less suitable to evaluate stage-transition in relation to cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…The transition to psychosis has been shown to occur according to a staging model much like the staging of the development of other medical disorders such as cancer and hypertension [42][43][44]. The staging has been proposed to be characterized by gender-specific factors [45,46].…”
Section: Discussionmentioning
confidence: 99%